NUMERICAL MODELLING OF GEOTHERMAL RESERVOIR IN GUNUNG TALANG, WEST SUMATERA, INDONESIA - Lia Putriyana; Hari Soekarno (JURNAL RISET GEOLOGI DAN PERTAMBANGAN, 2020)
Gunung Talang geothermal field is a part of Gunung Talang – Bukit Kili geothermal working area, which is located in Solok Regency, West Sumatera, Indonesia, about 54 km to the northeast of Padang city. A numerical model consisting of 1,680 grid blocks, covering an area of 17 km2 was developed for reservoir simulation. Two development strategies scenarios were constructed by considering various aspects such as reservoir behaviour, power plant’s lifetime, environmental effects, resources, and prospect area. The power plant’s power generation capacity and production lifetime of the scenarios are respectively 41,83 MW with 106 years production lifetime from the first scenario and 79,53 MW with 54 years production lifetime from the second scenario. Nowadays, the Gunung Talang – Bukit Kili geothermal working area is being auctioned with a potential power generation of 65 MW.ABSTRAK – Pemodelan numerik reservoir panasbumi di Gunung Talang, Sumatera Barat, Indonesia. Lapangan panas bumi Gunung Talang merupakan bagian dari Wilayah Kerja Panasbumi Gunung Talang – Bukit Kili yang terletak di Kabupaten Solok, Sumatera Barat, Indonesia, sekitar 54 km arah timurlaut Kota Padang. Model numerik yang terdiri dari 1.680 blok grid untuk area seluas 17 km2 dibuat untuk mensimulasikan reservoir. Dua skenario strategi pengembangan dibangun dengan mempertimbangkan beberapa aspek seperti perilaku reservoir, umur pembangkit, pengaruh terhadap lingkungan, sumber daya, dan area prospek. Kapasitas pembangkitan daya pembangkit listrik hasil skenario pertama adalah 41,83 MW dengan umur produksi 106 tahun, sedangkan skenario kedua menunjukkan kapasitas 79,53 MW dengan umur produksi 54 tahun. Saat ini, WKP Gunung Talang – Bukit Kili sedang dalam proses lelang dengan potensi pembangkitan listrik sebesar 65 MW.